2009
DOI: 10.1007/s00404-009-1220-z
|View full text |Cite
|
Sign up to set email alerts
|

Neuroaxial blocks and tattoos: a dilema?

Abstract: A tendency towards performing NB on pigment free skin, seems to exist. Literature has been the backup for anaesthetists confronted with the above scenario, while personal opinion seems to have been the basis for the remainders. The nonexistence of guidelines as well as the controversy regarding the risks involved in performing NB over tattoo, probably explain the diverse actions taken by the anaesthetists.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The risk of introducing pigments and the concern about the potential for tumor growth is currently under debate (Kluger, 2010). When surveyed, one study revealed that anesthesiologists preferred to inject through the nonpigmented skin if required to perform the procedure (Gaspar & Serrano, 2010). With little available evidence to support either method, it has been recommended to avoid piercing tattoos in the lumbar area for epidural access (Kuczkowski, 2006;Mercier & Bonnet, 2009;Welliver, Welliver, Carroll, & James, 2010).…”
Section: Body Artmentioning
confidence: 97%
“…The risk of introducing pigments and the concern about the potential for tumor growth is currently under debate (Kluger, 2010). When surveyed, one study revealed that anesthesiologists preferred to inject through the nonpigmented skin if required to perform the procedure (Gaspar & Serrano, 2010). With little available evidence to support either method, it has been recommended to avoid piercing tattoos in the lumbar area for epidural access (Kuczkowski, 2006;Mercier & Bonnet, 2009;Welliver, Welliver, Carroll, & James, 2010).…”
Section: Body Artmentioning
confidence: 97%
“…Over the last 20 years, some studies have raised issues related to the phenomenon of ‘coring’ when a CNB is performed in the presence (but also sometimes the absence) of tattoos 3–10. The tissue coring phenomenon is described as a possible entrainment of cells when there is any puncture of the skin 11.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted, however, that, to date, there are no published specialised reports that confirm late complications as a direct consequence of performing an epidural through a lumbar tattoo 6 8 10 20 21. Although millions of epidurals are performed worldwide, the number of epidurals through tattoos may still be very small, explaining the dearth of research on potential tattoo-related complications.…”
Section: Introductionmentioning
confidence: 99%
“…Of 162 anesthesiologists participating in the survey, 56.8% of the respondents said they preferred to place the neuraxial block through the clear skin, as they were not sure what the effects of the pigment would be when placed in the spinal canal. 9 Unlike Portuguese anesthesiologists, 57% of French anesthesiologists who were surveyed favored placing the epidural needle through the tattooed skin, and 70% felt that there was no consensus on this matter. 10 As there are no studies in the literature describing the effects of tattoo pigment introduced into the intrathecal space by needle puncture, we conducted this study in an animal model to determine the effects of such pigments on the meninges and the neural tissue and to infer the safety of such a practice.…”
mentioning
confidence: 99%